1969
DOI: 10.1021/es60029a001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of airborne particles with gases

Abstract: A promising method for making sorption measurements in aerocolloidal systems is described. Initial studies are being conducted on the interaction of sulfur dioxide with metal oxide aerosols. The latter are generated by exploding metal wires in air, resulting in particles with diameters from about 0.01 to 0.1 micron. These are mixed with S33-labeled S02 at controlled conditions in an 820-liter cylindrical chamber. Samples for analysis are withdrawn through diffusion tubes lined with leadperoxide-coated lead foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In previous central Pacific cruises, Cline and Bates (1983), Andreae and Raemdonck (1983), and measured DMS in surface water and found that the concentrations were highest within 5 ° of the Equator ('-'400 ng/L compared with < 100 ng/L at higher latitudes). Nevertheless, in the marine atmosphere, it is very likely that other existing com-pounds (e.g., oxides of Fe, A1, Ca) may catalytically expedite the oxidation (Urone et al, 1968;Smith et al, 1969). Hoyt's measurements of DMS on our cruise (private communication, California State Univeristy, San Luis Obispo) generally agreed with previous data.…”
Section: Formation Of Sulfate Aerosolssupporting
confidence: 86%
“…In previous central Pacific cruises, Cline and Bates (1983), Andreae and Raemdonck (1983), and measured DMS in surface water and found that the concentrations were highest within 5 ° of the Equator ('-'400 ng/L compared with < 100 ng/L at higher latitudes). Nevertheless, in the marine atmosphere, it is very likely that other existing com-pounds (e.g., oxides of Fe, A1, Ca) may catalytically expedite the oxidation (Urone et al, 1968;Smith et al, 1969). Hoyt's measurements of DMS on our cruise (private communication, California State Univeristy, San Luis Obispo) generally agreed with previous data.…”
Section: Formation Of Sulfate Aerosolssupporting
confidence: 86%
“…Thus, the presence of nuclei is a dominant factor in the formation and growth of aerosol. Smith et al (1969) studied reactions of SO, (no light source) with submicron particles of Fe304, A1203, lead oxides, and platinum. These particles were generated by an exploding-wire technique and were allowed to interact with sulfur-35-labeled SO, at ppm concentrations.…”
Section: Heterogeneous Reaction Systemsmentioning
confidence: 99%
“…An estimation of the quantity of sulfur dioxide sorbed on metal and metal oxide particles has been made by Smith et al (1969). Aerosols containing particles of FesO*, AI2O3, Pb02, or platinum in the size range of 0.01 to 0.1 µ were generated by the exploding wire technique.…”
mentioning
confidence: 99%